Environmentally Friendly Vocational Skills Learning Model Innovation for Self-Development of Students with Intellectual Disabilities - Kasirah, Irah; Trisna Mulyeni; Ningsih, Kholifatul Novita; Manar, Mayasari (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Education for students with intellectual disabilities presents its challenges, especially in meeting their needs for developing life skills. This research aims to create an environmentally friendly vocational skills learning model to increase the self-development of students with intellectual disabilities. This model was designed using the Research and Development (R&D) method involving teachers and students in SLB. This type of research is qualitative. The samples involved in this research were teachers and students at SLB. The data collection methods used were observation and field trials. Data were analyzed using Miles & Huberman's interactive analysis technique, which included data reduction, presentation, and concluding/verification. The research results show that this learning model can effectively increase student independence by making doormats from patchwork, which uses the concept of recycling. The learning process not only grows students' practical abilities, but also teaches the values of caring for the environment. In this research, the environmentally friendly vocational skills learning model developed is feasible and effective for improving the self-development of students with intellectual disabilities. This model was designed considering student characteristics, practice-based learning principles, and an inclusive and sustainable environmental approach. This research has implications for improving the quality of education in special schools by providing innovative environment-based learning alternatives.